Organizing Students’ Independent Work under the Guidance of a Foreign Language Teacher at the University - Zhetpisbayeva, B.A.; Ospanova, B.R.; Baideldinova, G.M.; Azimbayeva, Zh.A.; Akynzhanova, A.A. (Opcion, Año, 2019)
The article examines the actual problem of undergraduate students’ poor proficiency in foreign languages at non-linguistic universities. The purpose of this article is to develop and to test a technology for organizing students’ independent work under the guidance of a teacher of foreign language at a technical university, facilitating their perception of profession-oriented information. The study was based on the existing technology and the developed by us technology of organizing students’ independent work under the guidance of a teacher in teaching English as a foreign language in the first year at a polytechnic university. The study involved two groups: the control group was engaged in the existing technology of organizing students’ independent work under the guidance of a teacher, and the experimental group had classes on the developed by us technology of organizing students’ independent work under the guidance of a teacher. As a result of the work carried out at the developed by us technology of organizing students’ independent work under the guidance of a teacher which mandatory component is authentic foreign texts in specialties,special profession-oriented tasks for simple common texts of a foreign language and controlling-measuring profession-oriented materials, it was revealed that the proposed profession-oriented technology of organizing students’ independent work under the guidance of a teacher contributed to better proficiency and understanding of profession-oriented texts by students of technical specialties.
Keywords: foreign language; independent work under the guidance of a teacher; methodological guide; profession-oriented foreign language; specialists; technology of organizing independent work